ANALISIS PENANGANAN PEMBIAYAAN BERMASALAH DI LEMBAGA KEUANGAN SYARIAH (Studi Kasus di BMT Berkah Mandiri Sejahtera Cabang Cariu) - Siti Nuraeni; Mohammad Habibi (ICO EDUSHA, 2021)
Problematic financing often occurs in financial institutions both Islamic financial institutions and conventional financial institutions. The greater the problematic financing, it will have a bad impact on the level of liquidity health of financial institutions. This can also lead to a decrease in public trust to leave funds to financial institutions. Therefore, it is very important to draw up the right steps where a settlement is needed against problematic financing as a step of health and improvement to the balance sheet. In dealing with problematic financing every financial institution must have a different way. As one of the Islamic financial institutions, Baitul Maal wa Tamwil (BMT) Berkah Mandiri Sejahtera must have its own way to deal with troubled members in completing their financing. The purpose of this research is to find out the steps taken by BMT Berkah Mandiri Sejahtera in dealing with problematic financing. The method used in this study uses a type of qualitative research with a descriptive approach that aims to make descriptions, systematic, actual and accurate images of the facts, properties and relationships between the phenomena investigated and then conclude. This research data collection technique uses documents, interviews, and observations as a source of evidence to obtain data supported by conducting literature studies related to the regulation of problematic murabahah financing treatment. The results regarding problematic financing handlers in BMT Berkah Mandiri Sejahtera are by sending billing letters, monitoring, and withdrawal of guarantees. Keywords: billing, financing, monitoring, settlement. References Dr. Mardani, 2017 “ASPEK HUKUM LEMBAGA KEUANGAN SYARIAH DI INDONESIA” Jakarta: KENCANA. Eef Saefullah, Fitria Handayani, 2016, “IMPELEMENTASI FUNGSI BAYT AL- MĀL DAN PENGELOLAANNYA PADA BMT AL-FALAH SUMBER” Al- Amwal: Volume 8, No. 2 Mensari Rizki Dian, Dzikra Ahmad, 2017,“ ISLAM DAN LEMBAGA KEUANGAN SYARIAH”, AL-INTAJ Vol. 3, No. 1 Odi Nur Arifah, 2017, ANALISIS PEMBIAYAAN MUDHARABAH BERMASALAH PADA BMT MITRA HASANAH SEMARANG, Jurisprudence, Vol. 7 No. 1 Tita Novitasari, 2019, “Peran Otoritas Jasa Keuangan dalam Pengawasan Lembaga Baitul Maal wa Tamwil (BMT): Studi Kasus BMT Global Insani” Undang: Jurnal Hukum, Vol. 2, No. 1 Yanuar Dharma Putra, Imron Mawardi, 2019, “ELIMINASI RISIKO OPERASIONAL BMT SRI SEJAHTERA SURABAYA” Jurnal Ekonomi Syariah Teori dan Terapan: Vol. 6 No. 7